Populasi dan Sampel: Konsep dan Prosedur dalam Penelitian Pendidikan - Nur Isra' Ahmad; Supriadi (Yayasan Al-Afif, 2026)
Population and sample are methodological pillars that determine the quality of educational research. The problem raised is that there are still often ambiguities in defining the population and choosing a representative sample, so that the results of the research are at risk of bias and difficult to generalize. The purpose of this study is to analyze the definition of population and sample, the reason for sampling, and the proper sample determination procedure. The research method uses a library research approach by examining relevant literature. The results confirm that a population is a whole of objects with specific characteristics, while samples are chosen to represent the whole to make research efficient and relevant. The sampling procedure includes the determination of objectives, population, technique, and size, with more representative probability sampling and nonprobability sampling that is flexible but at risk of bias. Implicitly, researchers need to understand the concept of population and sample appropriately so that the research results are valid, can be used as a basis for policy, and are relevant to social dynamics and practical needs.